تحسين نظام MIMO-OFDM بزيادة معدل نقل البيانات (Latakia University Journal -Engineering Sciences Series, 2018)
The advanced developing of the wireless communications and its use in daily life raised the demands for more data rates equal to the wire networks. The third generations of the mobile network came to enhance the data rate but the continues growth of the media made the users grave for more. MIMO-OFDM system considered the core of the modern Telecommunication systems like 4G mobile networks and Wimax networks. In this article, we will study OFDM system with multiple sets of input- output antennas, and then enhance the system with bell lab vertical space-time algorithm V-BLAST combined with signal cancelling technics like Zero Forcing ZF and Minimum Mean Square Error MMSE. تحسين نظام MIMO-OFDM بزيادة معدل نقل البيانات إن تطور الاتصالات اللاسلكية السريع ودخولها إلى معظم جوانب الحياة دفع إلى الطلب المتزايد على سرعة نقل بيانات عالية تضاهي الاتصالات السلكية .وقد ظهر الجيل الثالث ليعزز معدل البيانات لكن التطور المستمر في تطبيقات الوسائط المتعددة جعل معدل البيانات المستخدم غيركاف. يعتبر نظام MIMO-OFDM اللبنة الاساسية في أنظمة الاتصالات الحديثة مثل شبكات الخليوي الجيل الرابع 4Gوشبكات Wimax , يتم التطرق في هذا البحث إلى دراسة نظام OFDM مطبق على عدد من هوائيات الدخل والخرج ومن ثم تحسينه بخوارزمية مخبر Bell الزمانية المكانية العموديةV-BLAST .مع احدى تقنيات الغاء الاشارات وهي التصفير القسري Zero Forcing ZF  والقيمة الصغرى لمتوسط مربع الخطأ MMSE.